2023
DOI: 10.1177/03331024231194024
|View full text |Cite
|
Sign up to set email alerts
|

Secondary headache disorders in Turkey, the Middle East, Asia, and Africa: A cross-sectional, multicenter study

Ahmet Evlice,
Hamit Genç,
Derya Uluduz
et al.

Abstract: Background This multicenter cross-sectional study aimed to determine the frequency and characteristics of secondary headaches in different geographic regions, including Turkey, the Middle East, Asia, and Africa. Methods Patients were admitted to the study on a particular day each week for five consecutive weeks between 1 April and 16 May 2022. Before the study, all researchers underwent a constructed briefing about the use and code of the ICHD-3 criteria. The study was conducted in two stages. In the first sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…The prevalence of secondary headache disorders was 1249/3722 (33%), with no remarkable differences within the studied regions. The most prevalent headache disorders were medication overuse headache (9%), idiopathic intracranial hypertension (3%), and cervicogenic headache (3%) [ 108 ].…”
Section: Secondary Headachesmentioning
confidence: 99%
“…The prevalence of secondary headache disorders was 1249/3722 (33%), with no remarkable differences within the studied regions. The most prevalent headache disorders were medication overuse headache (9%), idiopathic intracranial hypertension (3%), and cervicogenic headache (3%) [ 108 ].…”
Section: Secondary Headachesmentioning
confidence: 99%
“…Secondary headaches in particular constitute a matter of concern due to the limited availability of instruments for differential diagnosis. A recent cross-sectional investigation showed that approximately one-third of headaches were found to be secondary in African, Middle-East and Asian countries, the most common subtype of secondary headaches was headache attributed to substances or their withdrawal [60]. However, several primary causes exist that need to be ruled out with laboratory (e.g.…”
Section: Care Pathwaysmentioning
confidence: 99%
“…This entity is well studied and is categorized into eight different subtypes in the International Classification of Headache Disorders (ICHD) [3]. Hyperthyroidism is not listed amongst the most common causes of secondary headache in a study that included multiple centers located in Asia, Africa, The Middle East, and Turkey [4]. On the other hand, hyperthyroidism disorders like Graves' disease are also another highly prevalent entity; with the prevalence of suspected cases in Jeddah, Saudi Arabia, where the case to be reported is from, being 1.2% [5].…”
Section: Introductionmentioning
confidence: 99%